Nature as a Mode of Existence of Capital: Territorial Organization and the Dissolution of the Peasantry in Latin America’s Commodity Supercycle - Arboleda, Martín (2017)
This article addresses the processes of technological modernization that have taken place in Latin America’s mining industry, especially in the context of a new geography of late industrialization whose gravitational center has shifted towards East Asian economies. Through the Marxist critique of ecology, the paper explains the ways in which both human and nonhuman natures have been emptied of their concrete specificity in order to be transformed into the alienatedpowers of capital. The intensification in land use that has followed the robotization and computerization of large-scale mining has not only reconfigured the biogeophysical environment into a constitutive moment of the forces of production, but also entailed the systematic transformation of peasantries into dispossessed multitudes that act as mere appendages of technical systems of extraction, or as surplus populations. The reorganization of the mining industry into global supply chains requires rethinking extraction beyond primary commodity production, and interrogating its organic unity with the modern mode of production generally considered.